Tunable luminescence of a synthesized furophenanthraquinone derivative: interactions with different solvents. (30th January 2020) - Sarkar, Aparna; Pyne, Dinesh Kumar; Biswas, Tuyan; Das, Rumpa; Kar, Gandhi K.; Halder, Arnab
Abstract: The synthesis is described of a luminescent furophenanthraquinone derivative, 9‐methoxyphenanthro[4, 3‐ b ]furan‐4, 5‐dione (MPFD). The biological importance of tetracyclic furophenanthraquinones was considered and the tunable luminescence of MPFD in different solvents was studied to explore the nature of the specific interactions between MPFD and solvents. Observation of dual emission bands and identical nature of the fluorescence excitation spectra of MPFD monitored at the emission wavelength in polar solvents indicated the formation of two different types of species in the excited state, probably due to proton transfer from the solvent to MPFD. Luminescence intensity due to anionic species was found to be increased and the corresponding peak was red shifted with increase in the proton‐donating ability of the solvents, acting as an acid with respect to MPFD. Availability of more acidic protons in the solvent facilitated this phenomenon occurring in the excited state. MPFD also interacted with halogen‐containing solvents by forming electron donor–acceptor charge transfer (CT) complexes. This CT complex formation was dependent on the number of chlorine atoms; the position of the corresponding luminescence band varied with the polarity of the solvent. Extent of the CT increased with increase in the number of chlorine atoms in the dichloro, trichloro and tetrachloro solvents, whereas the luminescence peak due to the CT complex was found to be blue shifted with decrease in solvent polarity. Interaction of the synthesized bioactive MPFD with different solvents deserves biological importance as proton transfer and CT play pivotal roles in biology.